Pelatihan Pemanfaatan Fanspage Facebook Sebagai Sarana Media Informasi Kegiatan Di PKBM Belajar Pintar - Anggi Hadi Wijaya; Ipriadi (CV. ITTC INDONESIA, 2024)
The use of information technology (internet) today is no longer something strange. The internet has become a necessity, especially when linked to it as a means of real-time information. Almost all areas of life use the internet to disseminate and obtain the latest information, as is the case with PKBM Smart Learning in the city of Padang. The Smart Learning Community Learning Activity Center (PKBM) as an institution formed by the community that is active in education is of course very important in providing important information to the community. Is the information in the form of activities at PKBM Smart Learning or in the form of promotions from PKBM itself? One of the social media platforms in the form of a social network is Facebook. All the features of this Facebook Fanpage are very good for supporting the means of conveying the latest information from PKBM Belajar Kota Padang. Therefore, this community service is carried out to provide training in managing the PKBM Smart Learning Fanpage for Padang City